STUDI KOMPARASI TINGKAT KEBISINGAN PADA WAKTU BERBEDA DI SEKOLAH DASAR NEGERI MELAYU 2 BANJARMASIN - Agus Dian Mawardi; Saidah Tunnoor (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2020)
The research objective was to determine the Noise Level and the Difference in Noise Level at Different Times in SDN Melayu 2 Banjarmasin. The object of research is